13 Exposition Internationale de gravure 1979. - Krzisnik, Zoran; Mikuz, Jure; Pasmore, Victor; Rozic, Marjan; Stele-Mozina, Melita; Biennale Ljubljana 1979; Yoshiaki, Tono (Ljubljana : Moderna Galerija, 1979)
Abad, Francesc ; Al-Jumaie, Saleh ; Alberto, José ; Alima, Ritta ; Allen, George Victor ; De Almeida, David ; Alviani, Getulio ; Amano, Junji ; Amano, Kazumi ; Amimoto, Tomoyo ; Anderle, Jiri ; Angeli, Eduard ; Apollonio, Zvest ; Arakawa, Shusaku ; Araki, Tetsuo ; Arnal, Enrique ; Arsic, Miroslav ; Aschenbrenner, Lennart ; Atlanov, Jurij ; Avila, Efrain ; AY-O ; Azza, Hachmi ; Bagilhole, Robin ; Bakalov, Dimitar ; Barbarigo, Ida ; Bartlett, Jennifer ; Bartram, Edward ; Bassetti, Florenze ; Bates, Pat Martin ; Battegazzore, Miguel A. ; Baumgartner, René-Agass ; Belgeonne, Gabriel ; Beltran, Felix ; Benjamin, Anthony ; Benjano, Gabriel ; Bergman, Anna-Eva ; Berlinicke, Hartmut R. ; Bernik, Janez ; Bianchedi, Remo ; Blagovolin, Nikolaj ; Blinder, Olga ; Boetti, Alighiero ; Boljka, Janez ; Borcic, Bogdan ; Bose, Arun ; Bouca, António ; Bozidar, Jakac ; Brack, John ; Brajkov, Peter ; Brandstätter, Karl ; Brandt-Möller, Svend ; Braun, Herman ; Bravo, Javier Virseda ; Brocquy, Louis Le ; Browne, Gilbert ; Brunner, Michel ; Bucher, André ; Bulacu, Aurel ; Burri, Alberto ; Burwitz, Nils ; Caloenescu, Adina ; Capobianco, Domenick ; Carisnikov, Jurij ; Carmi, Eugenio ; Castellani, Enrico ; Cattelani, Raul ; Ceesay, Momodou ; Cereteli, Georgij ; Cernigoj, August ; Ceroli, Mario ; Charernsuphkul, Kanya ; Cheng, Mian ; Ciuha, Joze ; Clement, George Scott ; Clutterbuck, Jock ; Coen, Arnaldo ; Coita, Nistor ; Colombino, Carlos ; Comstedt, Maud ; Constantinou-Wilson, Anna ; Contaratou, Sosso ; Contte, Hector ; Corneille ; Cremer, Jan ; Cupic, Rada ; Curry, Gwen ; Czober, Tadeusz ; d'Almeida, Joao Bento ; Dahmen, Karl Fred ; Deck, François ; Dembo, Aleksander ; Dendrinou-Nicolaidou, Tonia ; Denes, Agnes ; Dewey, Lilibet ; Dewint, Roger ; Diaz-Cortes, Antonio ; etc.
biografie
Engels
Frans
boek
Keywords: Joegoslavië